MODERN FORMS OF FUTURE DESIGNERS PREPARATION TO THEIR PROFESSIONAL CAREER DEVELOPMENT - Аlekseeva Svitlana (Professional Pedagogics, 2017)
In the article the problem of use of the acmeological technologies for training of future designers to the development of a professional career in the system of vocational education is exposed, career and professional plans of young people, their ideas about professional career, criteria of its successful realization are analyzed. The use of these technologies in educational process is considered to be effective as personality zones of development of future specialists become the object of technology.